Key Locking of CRH3C EMUs and Maintenance Safety - HAO Ming-yuan; HAO Quan-li; LIU Yue-feng (机车电传动)
For guaranteeing safety of maintenance men and avoiding electric shock, key locking concept of the CRH3C high-speed EMUs was proposed and expounded on principle and process; at the meantime, safety idea what was called self safety, held and on duty by self was promoted.